2018
DOI: 10.1016/j.enbuild.2018.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying uncertainty in thermophysical properties of walls by means of Bayesian inversion

Abstract: We introduce a computational framework to statistically infer thermophysical properties of any given wall from in-situ measurements of air temperature and surface heat fluxes. The proposed framework uses these measurements, within a Bayesian calibration approach, to sequentially infer input parameters of a one-dimensional heat diffusion model that describes the thermal performance of the wall. These inputs include spatially-variable functions that characterise the thermal conductivity and the volumetric heat c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…which, from (15), yields constraint (12). Noting that the selection of α −1 n in (14) is determined by the data misfit of the particles, we refer to our regularisation strategy as the data misfit controller (DMC).…”
Section: Our Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…which, from (15), yields constraint (12). Noting that the selection of α −1 n in (14) is determined by the data misfit of the particles, we refer to our regularisation strategy as the data misfit controller (DMC).…”
Section: Our Contributionmentioning
confidence: 99%
“…For further details we refer the reader to [16], where the selection of α n according to (23) was implemented in a batch-sequential EKI framework to sequentially solve an inverse problem that arises in resin transfer moulding. The same EKI methodology was applied in [15] for parameter identification of the heat equation, including identification of thermal conductivity and heat capacitance given boundary measurement of heat flux. Both time-dependent applications tackled in [15,16] involved the inversion of small number of measurements (e.g.…”
Section: Eki As Gaussian Approximation In Linearised Bayesian Temperingmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al (2017) have derived the heat conductivity in the layer between the atmosphere and the soil surface, Choi et al (2018) have inferred soil thermal conductivity from a thermal response test, and Tran et al (2016) have inferred organic matter content from soil temperature, liquid water, and apparent resistivity data. Bayesian inference has been more widely applied in engineering (Kaipio and Fox, 2011) to estimate thermal properties of fins (Gnanasekaran and Balaji, 2013;Somasundharam and Reddy, 2017) and walls (De Simon et al, 2018;Rodler et al, 2019). While the above studies have shown promise in estimating thermal properties from time series of temperature, several challenges still remain, including the need for an approach that can assess the conditions under which such estimates are reliable.…”
Section: Introductionmentioning
confidence: 99%
“…Biddulph et al [49] proposed a method using Bayesian inference to estimate the parameters and this method was improved by Gori et al [50] [51]. De Simon et al [52] also applied Bayesian inference to quantify the estimation uncertainty of thermophysical properties of walls. Bienvenido et al [53] developed a multilayer perceptron to estimate the U -value with the correction for storage effects.…”
Section: State Of the Artmentioning
confidence: 99%